2023
DOI: 10.3389/fphar.2023.1033859
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-related genes signature and validation of differential expression and the potential targeting drugs in temporal lobe epilepsy

Abstract: Introduction: Temporal lobe epilepsy (TLE) is the most common subtype of epilepsy in adults and is characterized by neuronal loss, gliosis, and sprouting mossy fibers in the hippocampus. But the mechanism underlying neuronal loss has not been fully elucidated. A new programmed cell death, cuproptosis, has recently been discovered; however, its role in TLE is not clear.Methods: We first investigated the copper ion concentration in the hippocampus tissue. Then, using the Sample dataset and E-MTAB-3123 dataset, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Cuproptosis is a Cu-dependent form of cell death associated with mitochondrial metabolism. Multiple studies have shown a close association between cardioproptosis and the occurrence and progression of various diseases, such as atherosclerosis, pulmonary hypertension, epilepsy, and tumors ( 31 33 ). Additionally, patients with sepsis may have elevated levels of Cu ions in their body.…”
Section: Discussionmentioning
confidence: 99%
“…Cuproptosis is a Cu-dependent form of cell death associated with mitochondrial metabolism. Multiple studies have shown a close association between cardioproptosis and the occurrence and progression of various diseases, such as atherosclerosis, pulmonary hypertension, epilepsy, and tumors ( 31 33 ). Additionally, patients with sepsis may have elevated levels of Cu ions in their body.…”
Section: Discussionmentioning
confidence: 99%
“… 87 In Temporal lobe epilepsy, upregulated CRGs may promote peripheral CD4 + and CD8 + T cell infiltration into epileptic focus, which increases seizure frequency. 88 In patients with pancreatic adenocarcinoma, CRGs may drive the infiltration of antitumor components, such as activated CD4 + and CD8 + T cells, which are associated with longer survival. 89 Further, copper‐coated nanomaterial sticking to T cell membrane could target the triple‐negative tumour cells to promote cuproptosis, offering promising applications in tumour immunotherapy.…”
Section: The Role Of Essential Trace Elementsmentioning
confidence: 99%
“…In addition, cuproptosis‐related genes (CRGs) may influence T cell exhaustion phenotype and serve as effective prognostic indicators for lung adenocarcinoma 87 . In Temporal lobe epilepsy, upregulated CRGs may promote peripheral CD4 + and CD8 + T cell infiltration into epileptic focus, which increases seizure frequency 88 . In patients with pancreatic adenocarcinoma, CRGs may drive the infiltration of antitumor components, such as activated CD4 + and CD8 + T cells, which are associated with longer survival 89 .…”
Section: The Role Of Essential Trace Elementsmentioning
confidence: 99%
“…It may be suggested, then, that FDX1 is associated with the regulatory pathway of DEX [ 85 ]. Yang X. et al used the Enrichr database to analyze small molecules and drugs targeting the key cuproptosis protein in temporal lobe epilepsy (TLE), and found that chlorzoxazone and piperlongumine were the most likely to target cuproptosis genes and thus inhibit cuproptosis [ 86 ]. In addition, Jinke Huang.…”
Section: Cuproptosis Drugsmentioning
confidence: 99%